Sponsoring sufism - How Goverments Promote „Mystical Islam“ in their Domestic and Foreign Policies (Context: Journal of Interdisciplinary Studies, 2022)
Fait Muedini, Sponsoring sufism – How Goverments Promote „Mystical Islam“ in their Domestic and Foreign Policies, New York: Palgrave Macmillan US, 1. izdanje, 2015. Str. 219, ISBN 978-1-137-52107-1.